Jake makes a world : Jacob Lawrence, a young artist in Harlem - Rhodes-Pitts, Sharifa; Myers, Christopher; Lawrence, Jacob, 1917-2000. (2015)
"Jake Makes a World follows the creative adventures of the young Jacob Lawrence as he finds inspiration in the vibrant colors and characters of his community in Harlem. From his mother's apartment, where he is surrounded by brightly colored walls with intricate patterns; to the streets full of familiar and not-so-familiar faces, sounds, rhythms, and smells; to the art studio where he goes each day after school to transform his everyday world on an epic scale, Jake takes readers on an enchanting journey through the bustling sights and sounds of his neighborhood."--Provided by publisher
Keywords: Lawrence, Jacob, -- 1917-2000 -- Childhood and youth -- Juvenile fiction; Lawrence, Jacob, -- 1917-2000 -- Themes, motives -- Juvenile fiction; African Americans in art -- Juvenile fiction; Harlem (New York, N.Y.) -- In art -- Juvenile fiction